A high strength triboelectric nanogenerator based on rigid-flexible coupling design for energy storage system. (January 2020) - Xia, Kequan; Tang, Haichao; Fu, Jiangming; Tian, Yang; Xu, Zhiwei; Lu, Jianguo; Zhu, Zhiyuan
Abstract: Recently, efficient green energy conversion and storage systems attracts attention due to global environmental pollution and the depletion of fossil fuels. Here, we firstly proposed a novel triboelectric nanogenerator based on the rigid-flexible coupling design (RF-TENG) using the acrylate structure glue (ASG) and the silicic acid gel (SAG) as triboelectric materials. The fully packed ASG layer and SAG layer can be easily prepared by coating ASG/SAG on the Ni foam surface, and Ni foam plays the role of conductive electrode. Remarkably, the reasonable collocation of a rigid ASG layer and soft SAG layer can bring full and effective contact during the triboelectricity process for enhancing the output performance. Moreover, the RF-TENG can work in adverse environment. The corresponding electrical properties, such as the peak value short-circuit current ( I sc ), open-circuit voltage ( V oc ), and output power density can achieve 42 μA, 345 V, and 143 μW/cm 2, respectively, and 122 commercial light-emitting diodes (LEDs) can be easily lighted up by the RF-TENG. Except for that, an effective strategy for energy conversion and storage was designed, and through the proposed power management circuit (PMC), the charging efficiency of MnSe-Supercapacitor (MnSe-SC) has been significantly improved. Due to the high performance of energy conversion and storage, this research is considered promising for promoting the practical application of green energy. Graphical abstract: Image 1 Highlights: The ASG and SAG were firstly used as the triboelectric materials to fabricate a HS-TENG based on the rigid-flexible coupling design. The reasonable collocation of two triboelectric materials can enhance the output performance of TENGs, and the corresponding simulation results show the superiority of this design.(3) Considering the properties of the materials, such as withstanding dust/vibration, moisture-proof, waterproof functions, and corrosion resistance, the HS-TENG can work in adverse environment. The corresponding electrical properties, such as the peak value I sc, V oc, and output power density can achieve 42 μA, 345 V, and 143 μW/cm 2, respectively. Considering the matching between the internal impedance of supercapacitor and the output power of TENG, a commercial PMC using LTC-3588 chip was used to improve the charging efficiency for MnSe-SC.